Global Trends in Research of Macrophages Associated With Acute Lung Injury Over Past 10 Years: A Bibliometric Analysis - Wang, Sheng; Zhou, Huanping; Zheng, Li; Zhu, Wanli; Zhu, Lina; Feng, Di; Wei, Juan; Chen, Guannan; Jin, Xiaohong; Yang, Hao; Shi, Xuan; Lv, Xin (Frontiers in Immunology, 2021)
Acute lung injury (ALI) is an intractable disorder associated with macrophages. This bibliometric analysis was applied to identify the characteristics of global scientific output, the hotspots and frontiers about macrophages in ALI over the past 10 years. We retrieved publications published from 2011 to 2020 and their recorded information from Science Citation Index Expanded (SCI-expanded) of Web of Science Core Collection (WoSCC). Bibliometrix package was used to analyze bibliometric indicators, and the VOSviewer was used to visualize the trend and hotspots of researches on macrophages in ALI. Altogether 2632 original articles were reviewed and the results showed that the annual number of publications (Np) concerning the role of macrophages in ALI kept increasing over the past 10 years. China produced the most papers, the number of citations (Nc) and H-index of the USA ranked first. Shanghai Jiaotong University and INT IMMUNOPHARMACOL were the most prolific affiliation and journal respectively. Papers published by Matute-Bello G in 2011 had the highest local citation score (LCS). Recently, the keywords “NLRP3” and “extracellular vesicles” appeared most frequently. Besides, researches on COVID-19 induced ALI related to macrophages seemed to be the hotspot recently. This bibliometric study revealed that publications related to macrophages in ALI tend to increase continuously. China was a big producer and the USA was an influential country in this field. Most studies were mainly centered on basic researches in the past decade, and pathways associated with the regulatory role of macrophages in inhibiting and attenuating ALI have become the focus of attention in more recent studies. What’s more, our bibliometric analysis showed that macrophages play an important role in COVID-19 induced ALI and may be a target for the treatment of COVID-19.